Spectral domain and angiography optical coherence tomography in atypical parkinsonisms and Parkinson disease: an explorative study - Cennamo, Gilda; Di Maio, Laura Giovanna; Riccio, Gabriele; Coppola, Rosa; Baratto, Luigi; Giglio, Augusta; Manganelli, Fiore; De Michele, Giuseppe; Costagliola, Ciro; De Rosa, Anna (Parkinsonism & related disorders, 2025)
Research recently focused on identifying early and accurate biomarkers to differentiate Parkinson Disease (PD) from other degenerative parkinsonism, such as Progressive Supranuclear Palsy-Richardson Syndrome (PSP-RS) and Multiple System Atrophy (MSA). We aimed to investigate changes in the retinal structure and choroidal vascular network (CVN) in PSP-RS and MSA patients compared to PD and controls (Ctrl). Spectral Domain-Optical Coherence Tomography (SD-OCT) was used to examine the ganglion cell complex (GCC), retinal nerve fiber layer (RNFL) and subfoveal choroidal thickness, and OCT Angiography (OCTA) for the vessel area density (VAD) of retinal and CVN assessment. We analyzed 22 eyes from 11 PSP-RS, 14 from 7 MSA, 48 from 24 PD patients, and 50 from 25 Ctrl. In comparison to Ctrl, we observed decreased GCC thickness in PSP-RS (p = 0.001) and PD patients (p = 0.003), and reduced RNFL thickness in all three groups of patients (PD p = 0.043; PSP-RS p < 0.001; MSA p < 0.001). PD subjects showed lower values in VAD of superficial capillary plexus (p = 0.013) and radial peripapillary capillary plexus (RPCP) (p = 0.014) in comparison to Ctrl, whereas MSA and PSP-RS patients did not differ from them. Both groups presented significantly decreased RNFL thickness and higher VAD of RPCP in comparison to the PD group (p < 0.001). Compared to PD, the retina structural damage in PSP-RS and MSA appears to be similar but more severe, whereas the CVN appears to be preserved. Our preliminary results should be confirmed in a larger series of patients to test whether OCTA can be used to differentiate degenerative parkinsonisms. •SD-OCT and OCTA might be used as biomarkers to differentiate degenerative parkinsonism.•Retinal structure impairment in PSP-RS and MSA is more severe than in PD.•The choroidal vascular network seems to be preserved in PSP-RS and MSA patients in comparison to PD.